Assessing self-administration of medication: video-based evaluation of patient performance in the ABLYMED study - Luegering, Anneke; Langner, Robert; Wilm, Stefan; Doeppner, Thorsten R.; Hermann, Dirk M.; Frohnhofen, Helmut; Gronewold, Janine (Frontiers in Medicine, 2024)
Background: Older adults often face challenges in medication management due to multimorbidity and complex medication regimens, which frequently go unreported. Unrecognized problems, however, may lead to a loss of drug efficacy and harmful side effects. This study aimed to quantify the prevalence of such problems by applying a novel video-based assessment procedure in a sample of elderly patients.In this study, 57 elderly in-patients (≥70 years old and regularly taking ≥5 different drugs autonomously) from the ABLYMED study participated in a placebo-based assessment of medication management with five different dosage forms in an instructed manner while being filmed. Patient performance was quantified by the median value of two raters who evaluated each step of medication administration, which were summed to sum scores for each dosage form and an overall impression for each dosage form with a standardized and previously validated rating scheme.The median (Q1;Q3) sum score for tablets was 7.0 (5.0;8.0) with a theoretical range between 4.0 and 17.0, for eye-drops 1.5 (1.0;2.0) with a theoretical range between 1.0 and 5.0, for oral drops 4 (3.0;5.8) with a theoretical range between 3.0 and 12.0, for pens 6.5 (4.5;9.3) with a theoretical range between 4.0 and 20.0 and for patches 4.5 (4.0;6.5) with a theoretical range between 3.0 and 15.0. The most difficult step of medication administration was peeling off the protective liner of a patch: 30% had severe difficulties or it was not possible, 21% had moderate difficulties and 49% had mild or no difficulties.Discussion: In a sample of patients with autonomous medication management, our novel assessment procedure identified a substantial fraction of patients with handling problems for each dosage form. This suggests that patients´ medication management problems should be assessed regularly in clinical routine and tackled by patient-individual training or modification of the prescribed drug regimens to achieve effective drug therapy in the elderly.